Bioengineering of novel organotypic 3D human liver tissue model for drug-induced liver injury and toxicity studies - Holm, Camden; Finelli, Joseph; Frare, Mateo; Armento, Alex; Ayehunie, Seyoum (Frontiers in Toxicology, 2025)
BackgroundIn drug development, liver failure is the cause of approximately 30% of post marketing withdrawals of pharmaceuticals. Drug-induced liver injury (DILI) remains the leading cause of acute liver failure (ALF), accounting for approximately 15% of the cases.Materials and methodsIn this study, we developed a novel human three-dimensional (3D) liver tissue model by seeding adult primary human hepatocytes onto cell culture inserts under Air-Liquid Interface (ALI) condition for extended culture periods. The engineered tissues were thoroughly characterized for barrier integrity using transepithelial electrical resistance (TEER) measurements and assessed for tissue morphology and structure via hematoxylin and eosin (H&E) staining and immunohistochemistry. Expression levels of drug transporters and drug-metabolizing enzymes were evaluated by quantitative PCR (qPCR). The functionality of the tissue model for drug toxicity assessment was demonstrated by comparison with conventional two-dimensional (2D) monolayer hepatocyte cultures and liver spheroids. To evaluate the model's relevance for DILI studies, we exposed the 3D liver tissues to compounds with well-documented hepatotoxic profiles in humans. Liver function was monitored by quantifying biomarkers such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST) released into the culture medium.ResultsThe engineered 3D liver tissue model exhibited distinct apical and basolateral surfaces, reflecting a polarized and stratified architecture that closely mimics native liver tissue. Morphological and phenotypic analyses confirmed the tissue's organotypic features. Gene expression profiling revealed elevated levels of liver-specific genes involved in drug transport, metabolism, and clearance. Functionally, the tissue metabolized midazolam–a substrate of the cytochrome P450 3A4 (CYP3A4) enzyme–into its primary metabolite, 1-hydroxymidazolam. Upon repeated exposure to fialuridine, a discontinued anti-hepatitis B drug known for causing severe liver toxicity in humans, the tissue model exhibited barrier compromise, reduced albumin production, and increased levels of ALT and AST in a time- and concentration-dependent manner.DiscussionThe results strongly suggest the model's physiological relevance and functionality in predicting drug responses in humans. Thus, the engineered 3D organotypic human liver tissue model which can be cultured for weeks and produced in a semi-high throughput format creates an opportunity to study drug-induced liver toxicity in an in vitro microenvironment. The reconstructed 3D liver tissue model can serve as a tool for alternative methods intended to reduce animal use in experimentation.